2017
DOI: 10.1002/pnp.466
|View full text |Cite
|
Sign up to set email alerts
|

Patients' experiences of and attitudes towards ECT

Abstract: Since its introduction electroconvulsive therapy (ECT) has received varied responses from the public and the media. Even though it is an effective treatment, its use has been restricted to very few serious psychiatric disorders. In this paper, Dr Guruvaiah and colleagues capture patients' and their carers' positive experience and attitude towards ECT following their treatment, which can act as reassurance for patients undergoing this efficacious therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
(10 reference statements)
2
7
0
Order By: Relevance
“…There were statements by participants that ECT gave them their lives back again and, for some, this meant that they did not commit suicide; this aligns with accounts reported in other studies [5]. The exclusively positive experiences relayed by participants provide evidence opposing the negative view portrayed in the media [11][12][13]20] and on some internet sites [10]. It is important that the public have a chance to understand the experience of people who undergo ECT in the NHS today, and that the media provides a balanced and accurate portrayal of ECT [31].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…There were statements by participants that ECT gave them their lives back again and, for some, this meant that they did not commit suicide; this aligns with accounts reported in other studies [5]. The exclusively positive experiences relayed by participants provide evidence opposing the negative view portrayed in the media [11][12][13]20] and on some internet sites [10]. It is important that the public have a chance to understand the experience of people who undergo ECT in the NHS today, and that the media provides a balanced and accurate portrayal of ECT [31].…”
Section: Discussionsupporting
confidence: 80%
“…Recent surveys of patients who have undergone ECT treatment have revealed positive attitudes to its effectiveness [20][21][22]. In one study, less than a fifth of respondents rated ECT as slightly as or much worse than going to the dentist [21] Review Patient Reported Experience of Electro Convulsive Therapy (ECT)…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported subjective rates of memory loss: 30 patients were interviewed and 80% reported memory loss, 389 respondents were surveyed and 50% reported memory loss, 51 patients were surveyed and 60% reported memory impairment, and 108 patients were questioned and 45% reported persistent memory loss (15, 16, 29, 30). However, a review of subjective memory complaints—assessed mostly on the Squire Subjective Memory Assessment—found the majority of studies reporting improved subjective memory after ECT (31).…”
Section: Resultsmentioning
confidence: 99%
“…There are also short-term side effects that may occur immediately after treatment, including drowsiness, confusion, headache, sickness, and aching muscles (29, 30). Both immediate and longer-term side effects can negatively impact on patient’s perspectives of ECT, but patients are likely to consider that they are acceptable if they are outweighed by the antidepressive benefits of ECT; patients engage in a “cost–benefit analysis” (16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation